Dimensional Changes in Peri-implant Buccal Bone and Soft Tissue in Grafted and Native Bone: Preliminary Results of an Ongoing Prospective Study in Humans - Li, Min-Yin. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Periodontology.; Advisor: Yumi Ogata.; Committee: Yong Hur, Martyn Green, Rumpa Ganguly, and Sarah Pagni.; Keyword: Dentistry.